Awareness and preparedness for disasters amongst residents in dry, hilly, and delta regions of Myanmar - Soe, Pa Pa; Hlaing, Thein; Hnin, Zar Lwin (International Journal Of Community Medicine And Public Health, 2022)
Background: Because of Myanmar’s location, many residents are in disaster risk zones. This study aimed to explore the disaster-related awareness and preparedness of the residents from the dry, hilly, and delta regions. Methods: This research was a survey design, a cross-sectional approach, and used a survey questionnaire. By applying the RCDP clusters and hazard profile, 13 (19%) villages from hilly, 100 (53%) villages from dry, and 27 (28%) villages from the delta region were proportionately and randomly selected. From which,1800 household heads were randomly culled. The data collected through the face-to-face interview were entered into EpiData and analyzed in STATA 15. Results: All samples of residents were composed of 6.7% from hilly, 76.5% from dry, and 16.8% from the delta region. Residents of 72.4% and 71.5% (dry region), 54.3% and 53.4% (hilly region), and 88.6% and 87.6% (delta region) were aware of the types and associated risks of the common disasters, respectively. Regarding disaster preparedness, approximately one-third have prepared for evacuation, emergency response, disaster kits, safe areas (shelter), reconstruction/rehabilitation, about one-fifth for emergency response operations, risk assessment, and risk reduction planning, and less than 10% for capacity building, awareness-raising, and information management. More than 50% have planned for preparedness after returning homes. Overall, good awareness and preparedness proportions were 38.2% and 13.9%. Conclusions: Overall, the three regions’ disaster awareness and preparedness levels were unsatisfactory, which highlights that National Natural Disaster Management Committee should effectively apply the information media, provide training/advocacies and support safe community initiatives.